Governing a more global world - Aart Scholte, Jan (Corporate governance (Bradford), 2010)
Purpose - This paper aims to clarify the character of globalization, to identify the changes it brings to structures of governance, and to consider ways in which these arrangements could be made to serve a good (more global) society.Design methodology approach - This essay takes a reflective approach.Findings - The paper considers the rules and regulatory processes that govern today's more global world. The first step in the analysis identifies globalization as a trend whereby people's lives become more interconnected on a planetary scale. The second section describes the institutional apparatuses through which global issues are governed. Global governance is seen to take shape not as a "world government", but as a complex array of regulatory networks that span local to global scales and also combine public and private sectors. The third section assesses the normative values that this "networked" and "polycentric" governance of global affairs might serve. Both an earlier "neoliberal" design of global governance and a currently prevailing "social market" paradigm are critiqued. An alternative vision of global social and ecological democracy is offered as a more promising road to a good society in the contemporary more global world.Practical implications - The paper suggests alternative guiding principles for governance of today's more global society, including the role of corporations in it.Social implications - The paper suggests ways in which global governance can deliver social justice, ecological sustainability and democracy along with material prosperity.Originality value - The paper consolidates a conception of post-statist governance that can aid researchers and practitioners alike in mapping the processes of contemporary policymaking. The normative framework presented can, moreover, help to clarify the objectives that citizens of a more global world would wish regulation to provide.